2021
DOI: 10.24928/2021/0154
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Framework for Systemic Transformation of the Construction Industry

Abstract: In the era of customer-driven and digitalized businesses, the construction industry has still demonstrated inadequate performance development. This research aims to disentangle the industry's current problems and present justified paths toward sustainable improvement. Following the design science research approach, the paper develops a conceptual framework about the path toward the systemic transformation of the construction industry. We first argue how current efforts to improve construction system are often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Lehtovaara et al (2020) developed a maturity level model that describes how the development of an organization's takt production capability can be used to connect and implement many other lean construction concepts. Peltokorpi et al (2021) identified takt production as one key driver for systemic change and suggested a conceptual framework of integrating a set of sub-systems present in construction, that need to be developed together in order to achieve sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…Lehtovaara et al (2020) developed a maturity level model that describes how the development of an organization's takt production capability can be used to connect and implement many other lean construction concepts. Peltokorpi et al (2021) identified takt production as one key driver for systemic change and suggested a conceptual framework of integrating a set of sub-systems present in construction, that need to be developed together in order to achieve sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, government has pushed for the adoption of "Modern Methods of Construction" (a euphemism for off-site fabrication (OSF) and prefabrication) to help solve the housing shortage ( Jang, et al, 2021). In the US, companies like Katerra (while it was still trading), Project Frog, RAD Urban, Digital Building Components (Hall, Whyte and Lessing, 2020) and Brydon Wood in the UK (Peltokorpi, et al, 2021) all use prefabrication. Their apparent success puts pressure on the sector.…”
Section: Introductionmentioning
confidence: 99%